The sapnish constituent assembly and its constitutional result: The Constitution of 1978 - Contreras Ugarte, Jesús Víctor Alfredo (Derecho Público Iberoamericano, 2021)
Currently, especially in American countries, there is much talk of the need to change the Constitution through a Constituent Assembly. This, because it is evident that, in these countries, there is a change in the trend towards left-wing ideology that, to be fair to the truth, warns us of a certain interest, support and agreement –which seems more like an international collusion of a certain sector– than it goes beyond the national scope of each country. It is this ideology, especially in the Ibero-American countries, which promotes, today, the total change of their constitutions, enabling and trying to accept and elect a Constituent Assembly that allows a radical change in search of its goals. Chile and Peru are good examples of this current phenomenon. In such an international context, I analyze, in this work, in the present, what was the Spanish constituent process that lead to the 1978 Spanish Constitution...